Masjid Tuha Indrapuri: Memahami Jejak Peninggalan Masa Lalu Melalui Desain yang Beridentitas - Rifqi DK; Carissa Alzena; Nurul Firdaus; Najla NS; Ismi Rahmatika; Karima Adilla; Izziah (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
Architecture is both art and science related to the design and construction of buildings and spaces to meet human needs. In a cultural context, architecture not merely reflects practical functions but also the aesthetic, social, and spiritual values upheld by society. Each building carries a story and deep meaning, which can be seen in its design, materials, and construction techniques. The Indrapuri old mosque, as an example of architecture rich in historical and cultural value, shows how architecture can reflect the historical journey of a region.